COMPORTAMENTO DE BOVINOS CONFINADOS RECEBENDO DIETAS COM DIFERENTES ADITIVOS - CORRÊA, Matheus Simão (matheuscorrea1084@hotmail.com,; FERNANDES, Henrique Jorge,; CANUTO, Nelson Guimarães Dantas, (ANAIS DO ENIC, 2023)
-